Floristic diversity and vegetation analysis of the community forests of South-West Haryana, India - Saharan, Harikesh; Dhiman, Himanshi; Jakhar, Somveer (Current Botany, 2020)
Community forestry is an important form of forests and provides resources to over a half billion people in developing countries. They also play a significant part in mitigating the CO2 levels by sequestering a significant amount of carbon in the soil as well as biomass. The present paper assessed floristic diversity and vegetation structure in three different community forests of southwest Haryana which is a part of tropical dry deciduous forests. The vegetation sampling and data analysis were done following standard procedures. A total of 76 plant species belonging to 37 families in the form of 11 trees, 13 species of shrubs, 46 species of herbs, and 6 species of climbers are documented from all three sites. Poaceae was the most specious family in three sites. The highest tree diversity was recorded in Bhera forest followed by Daya and Dhanger. Regarding understory, the forest of Daya has a greater diversity than Bhera and Dhanger forests. Salavadora oleoides was the dominant tree species in Daya site and Dhanger site while in Bhera the dominant tree species was Ailanthus excelsa. The incidence of rampant livestock grazing and other anthropogenic disturbances were visible in all three sites which are primarily responsible for the degradation of these already fragmented village community forests.